Numerical and Experimental Analysis of Gas Flow in a Coaxial Nozzle Applied to Directed Energy Deposition (DED) (International Journal of Engineering Materials and Manufacture, 2021)
create a melt pool on the substrate. A nozzle is used to carry metal powder within a gas flow until the melt pool, concentrating the flow at the same point. Coaxial nozzles usually have also a shield gas flow to prevent oxidation and an internal flow to protect the optical system. A right flow configuration must be selected to avoid high turbulence at the nozzle exit, leading to an efficient, inexpensive, and high-quality process. Due to the complexity of the process, CFD – Computer Fluid Dynamics are becoming necessary to understand the behaviour of those gas flows in DED processes. CFD can offer results close to reality and may allow an optimization of the whole nozzle designs, besides selecting the best gas flows for each application.The present work develops a CFD simulation of the gas flow behaviour in a coaxial nozzle with three internal annular channels (internal, carrier and shield). An initial set of gas flow was selected, based on previous experience of the manufacturer, and then improved. It searches for the low gas consumption, to form a focal point coinciding with the laser focus and a low velocity, which favours the deposition quality. To check the accuracy of the proposed CFD model, experimental measurements of gas velocity were performed and compared with simulated results.